Spirooxindole Derivative SOID-8 Induces Apoptosis Associated with Inhibition of JAK2/STAT3 Signaling in Melanoma Cells - Tian, Yan; Nam, Sangkil; Liu, Lucy; Yakushijin, Fumiko; Yakushijin, Kenichi; Buettner, Ralf; Liang, Wei; Yang, Fan; Ma, Yuelong; Horne, David; Jove, Richard (PLOS ONE, 2012)
Melanoma is generally refractory to current chemotherapy, thus new treatment strategies are needed. In this study, we synthesized a series of spirooxindole derivatives (SOID-1 to SOID-12) and evaluated their antitumor effects on melanoma. Among the 12 spirooxindole derivatives, SOID-8 showed the strongest antitumor activity by viability screening. SOID-8 inhibited viability of A2058, A375, SK-MEL-5 and SK-MEL-28 human melanoma cells in a dose- and time-dependent manner. SOID-8 also induced apoptosis of these tumor cells, which was confirmed by positive Annexin V staining and an increase of poly(ADP-ribose) polymerase cleavage. The antiapoptotic protein Mcl-1, a member of the Bcl-2 family, was downregulated and correlated with SOID-8 induced apoptosis. In addition, SOID-8 reduced tyrosine phosphorylation of Signal Tansducer and Activator of Transcription 3 (STAT3) in both dose- and time-dependent manners. This inhibition was associated with decreased levels of phosphorylation of Janus-activated kinase-2 (JAK2), an upstream kinase that mediates STAT3 phosphorylation at Tyr705. Accordingly, SOID-8 inhibited IL-6-induced activation of STAT3 and JAK2 in melanoma cells. Finally, SOID-8 suppressed melanoma tumor growth in a mouse xenograft model, accompanied with a decrease of phosphorylation of JAK2 and STAT3. Our results indicate that the antitumor activity of SOID-8 is at least partially due to inhibition of JAK2/STAT3 signaling in melanoma cells. These findings suggest that the spirooxindole derivative SOID-8 is a promising lead compound for further development of new preventive and therapeutic agents for melanoma.